Large Corpora and Historical Syntax: Consequences for the Study of Morphosyntactic Diffusion in the History of Spanish - Octavio de Toledo y Huerta, Álvaro S. (Frontiers in Psychology, 2019)
Abstract: Over the turn of the 21st century, the use of data from large electronic corpora has changed research on Spanish historical syntax, spurring interest in long-range evolutions and the shape of the correspondent diachronic curves. However, general reflections on diffusion and the factors that drive and influence it are still pretty much lacking. In this paper, I reflect on the research possibilities laid open by the availability of such large masses of data, focusing particularly on new knowledge on syntactic change brought about by the study of low-frequency phenomena and of recessive changes, as well as on the exploration of changes conditioned by dialect contact and textual traditions. I conclude with some remarks on the general typology of diffusion in syntactic change.